Green and environment-friendly ceramic body mud and manufacturing method thereof
By rationally preparing ceramic clay, adding specific raw materials and adopting specific processes, the problem of poor degradation performance and flexural strength of ceramic clay is solved, and efficient degradation and outstanding flexural strength of ceramic clay is achieved.
Patent Information
- Application Number
- CN202411952441.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The degradation performance and flexural strength of existing ceramic sludge are both poor, making it difficult to find a balance between environmental protection and practical application.
By reasonably preparing ceramic mud, adding raw materials such as β-tricalcium phosphate, iron powder, starch and phenolic resin, and using ball milling, drying, hot pressing molding and other processes, ceramic mud with good degradability and flexural strength is formed.
It realizes efficient degradation of ceramic clay and outstanding flexural strength, meeting the dual needs of environmental protection and practical application.
Smart Images

Figure BDA0005215164520000021 
Figure BDA0005215164520000051 
Figure BDA0005215164520000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to green and environmentally friendly ceramic clay and a manufacturing method thereof. Background Art
[0002] With the increasing awareness of environmental protection and the concept of sustainable development, the ceramic industry is facing unprecedented challenges and opportunities. Traditional ceramic green clay usually has the problem of poor degradation performance. In the natural environment, this kind of green clay is difficult to decompose by itself. A large number of discarded ceramic products made from green clay are piled up for a long time, which not only occupies precious land resources, but also causes potential harm to ecological and environmental elements such as soil and water. The landfill or incineration treatment of ceramic products is also not good. Landfill will lead to long-term occupation of land resources and decline in soil quality, and incineration may produce harmful gas emissions to pollute the atmospheric environment. Therefore, neither is a good way to degrade ceramic green clay. In addition, the mechanical properties of ceramic green clay, especially the flexural strength, also play a decisive role in its practical application. In the use of ceramic products, whether it is daily handling, placement or subjecting to certain external pressure or impact, the green clay is required to have sufficient flexural strength to maintain its structural integrity. If the flexural strength is insufficient, ceramic products are prone to fracture and damage, which will reduce their service life and safety of use, and limit the application and expansion of ceramic products in more fields.
[0003] At present, the existing ceramic clay on the market can only meet one performance, that is, good degradation performance but weak flexural strength. Therefore, it is of great practical significance to provide a ceramic clay with both excellent degradability and flexural strength. Summary of the invention
[0004] The purpose of the present invention is to provide a green and environmentally friendly ceramic clay and a method for manufacturing the same, which solves the problems of poor degradability and flexural strength of the ceramic clay in the prior art.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A green and environmentally friendly ceramic green mud, the ceramic green mud specifically comprises the following raw materials in parts by weight:
[0007]
[0008] As a preferred technical solution of the present invention, the limestone was purchased from Shandong Shouhua Chemical Co., Ltd.; the cordierite powder was purchased from Shijiazhuang Guangning Mineral Products Co., Ltd., item number bf011.
[0009] As a preferred technical solution of the present invention, the main chemical raw material composition of the shale powder is / wt.%: SiO279.73, Al2O39.92, Fe2O33.72, TiO20.57, CaO 0.67, MgO 2.03, K2O 0.04, Na2O 0.92, and others 2.40.
[0010] As a preferred technical solution of the present invention, the main chemical raw material composition of the slag is / wt.%: SiO274.90, Al2O311.75, Fe2O31.37, TiO20.55, CaO 2.13, MgO 0.96, K2O 5.17, Na2O 1.96, and others 1.21.
[0011] As a preferred technical solution of the present invention, the main chemical raw material composition of the wollastonite ore is / wt.%: SiO2 42.16, Al2O3 0.69, Fe2O3 0.67, TiO2 0.01, CaO 44.90, MgO 1.63, K2O 0.11, and others 9.83.
[0012] As a preferred technical solution of the present invention, the average particle size of the β-tricalcium phosphate is 360nm; the iron content of the iron powder is 99.9%; the starch is soluble starch with an average particle size of 60 mesh, purchased from Hubei Xinrunde Chemical Co., Ltd.; the phenolic resin is a thermosetting phenolic resin, model 2127, purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0013] Furthermore, the ceramic clay also includes anhydrous ethanol.
[0014] A method for manufacturing green and environmentally friendly ceramic clay comprises the following steps:
[0015] S1, grinding limestone, cordierite powder, shale powder, slag, wollastonite ore and iron powder with a planetary ball mill, sieving, and drying under temperature control to obtain a dry mixed material; stirring anhydrous ethanol and phenolic resin to obtain a mixed material;
[0016] S2, the dry mixture, β-tricalcium phosphate and starch are mixed evenly, ground, sieved, anhydrous ethanol is added, stirred evenly and shaken, and then the mixture is added to a temperature-controlled water bath and stirred until the anhydrous ethanol evaporates, and the temperature is controlled and dried to obtain an intermediate ceramic green mud;
[0017] S3, placing the intermediate ceramic green body in a mold, flattening the mold, heating the mold, controlling the pressure to form the green body through hot pressing and maintaining the pressure, and then sintering the green body under nitrogen protection to obtain a finished ceramic green body.
[0018] As a preferred technical solution of the present invention, in the planetary ball mill in step S1, the ratio of material: ball: water is 1:1.2-2:1, and the ball milling time is 30-60 min; the usage ratio of anhydrous ethanol and phenolic resin is 2 mL:1-1.5 g.
[0019] As a preferred technical solution of the present invention, the screening in step S1 is through a 50-mesh sieve; and the temperature of the temperature-controlled drying is 95-100°C.
[0020] As a preferred technical solution of the present invention, the amount of anhydrous ethanol added in step S2 is 1.4-1.8 times the total mass of the dry mixture, β-tricalcium phosphate and starch.
[0021] As a preferred technical solution of the present invention, the screening in step S2 is through an 80-mesh sieve; the temperature of the temperature-controlled water bath stirring is 80-85°C; and the temperature of the temperature-controlled drying is 85-90°C.
[0022] As a preferred technical solution of the present invention, in step S3, the mold is heated to 145-150° C.; the pressure of the controlled pressure hot pressing molding and holding pressure is 16-18 MPa, and the time is 30-35 min.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention adds β-tricalcium phosphate and iron powder, and the good biodegradability, biocompatibility and bio-nontoxicity of β-tricalcium phosphate and the good processability, degradability and biocompatibility of iron powder work synergistically to make the finished clay degradable to a certain extent; at the same time, starch is added as a pore-forming agent, so that the interior of the clay has a large number of uniform interconnected pore structures, and the existence of such structures in the system improves the degradability of the obtained clay; in addition, in order to ensure the stability of the pore structure, the present invention also adds phenolic resin. During the continuous heating process of the system, the glassy carbon network generated by the phenolic resin plays a good supporting role in the pore structure of the finished clay, thereby enhancing the degradability of the finished clay.
[0025] (2) The present invention uses limestone, cordierite powder, shale powder, slag and wollastonite as the main raw materials and adjusts the ratio of each raw material in the formula to produce a ceramic green mud product with excellent degradation performance. At the same time, the ceramic green mud also has outstanding flexural strength. Specifically, limestone is used to strengthen the skeleton, cordierite powder is used to improve the density and strength of the ceramic, shale powder is used to introduce more silicon dioxide to form a multi-element low-melting compound with the other raw materials in the system at high temperature, which is beneficial to the nucleation and growth of crystals in the liquid phase; alkali metal oxides are introduced with slag and wollastonite to promote the process of liquid phase sintering; therefore, the five can work together to make the obtained green mud have outstanding flexural strength. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The limestone used in the embodiment of the present invention was purchased from Shandong Shouhua Chemical Co., Ltd.; the cordierite powder used was purchased from Shijiazhuang Guangning Mineral Products Co., Ltd., item number bf011; the starch used was soluble starch, with an average particle size of 60 mesh, purchased from Hubei Xinrunde Chemical Co., Ltd.; the phenolic resin used was a thermosetting phenolic resin, model 2127, purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0028] The main chemical raw material composition of the shale powder used / wt.%: SiO279.73, Al2O39.92, Fe2O33.72, TiO20.57, CaO 0.67, MgO 2.03, K2O 0.04, Na2O 0.92, others 2.40; the main chemical raw material composition of the slag used / wt.%: SiO274.90, Al2O311.75, Fe2O31.37, TiO20.55, CaO 2.13, MgO 0.96, K2O5.17, Na2O 1.96, others 1.21; the main chemical raw material composition of the wollastonite ore used / wt.%: SiO242.16, Al2O30.69, Fe2O30.67, TiO20.01, CaO 44.90, MgO 1.63, K2O 0.11, others 9.83;
[0029] The average particle size of the β-tricalcium phosphate used is 360nm; the iron content of the iron powder used is 99.9%;
[0030] The above will not be elaborated further.
[0031] Example 1
[0032] A green and environmentally friendly ceramic green mud, the ceramic green mud specifically comprises the following raw materials in parts by weight:
[0033]
[0034] The ceramic green mud also includes anhydrous ethanol.
[0035] The green and environmentally friendly method for manufacturing ceramic clay specifically comprises the following steps:
[0036] S1, grinding limestone, cordierite powder, shale powder, slag, wollastonite ore and iron powder with a planetary ball mill for 30 minutes, passing through a 50-mesh sieve, and drying at 100° C. to obtain a dry mixed material; stirring anhydrous ethanol and phenolic resin uniformly to obtain a mixed material;
[0037] In the planetary ball mill, the material: ball: water = 1:1.2:1; the usage ratio of anhydrous ethanol and phenolic resin is 2mL:1.3g;
[0038] S2, the dry mixture, β-tricalcium phosphate and starch are mixed evenly, ground, passed through an 80-mesh sieve, anhydrous ethanol is added, stirred evenly and shaken, and then the mixture is added to a water bath controlled at 85° C. and stirred until the anhydrous ethanol evaporates, and then the temperature is controlled at 85° C. and dried to obtain an intermediate ceramic green mud;
[0039] The amount of anhydrous ethanol added is 1.4 times the total mass of the dry mixture, β-tricalcium phosphate and starch;
[0040] S3, placing the intermediate ceramic green body in a mold, pressing it flat and heating the mold to 145°C, hot pressing it at a controlled pressure of 16 MPa and maintaining the pressure for 35 minutes, and then sintering it under nitrogen protection to obtain a finished ceramic green body.
[0041] Example 2
[0042] A green and environmentally friendly ceramic green mud, the ceramic green mud specifically comprises the following raw materials in parts by weight:
[0043]
[0044] The ceramic green mud also includes anhydrous ethanol.
[0045] The green and environmentally friendly method for manufacturing ceramic clay specifically comprises the following steps:
[0046] S1, grinding limestone, cordierite powder, shale powder, slag, wollastonite ore and iron powder by planetary ball mill for 45 minutes, passing through a 50-mesh sieve, and drying at 95° C. to obtain a dry mixed material; stirring anhydrous ethanol and phenolic resin uniformly to obtain a mixed material;
[0047] In the planetary ball mill, the ratio of material: ball: water is 1:2:1; the usage ratio of anhydrous ethanol and phenolic resin is 2mL:1g;
[0048] S2, the dry mixture, β-tricalcium phosphate and starch are mixed evenly, ground, passed through an 80-mesh sieve, anhydrous ethanol is added, stirred evenly and shaken, and then the mixture is added to a water bath at 80°C and stirred until the anhydrous ethanol evaporates, and then the temperature is controlled at 90°C and dried to obtain an intermediate ceramic green mud;
[0049] The amount of anhydrous ethanol added is 1.6 times the total mass of the dry mixture, β-tricalcium phosphate and starch;
[0050] S3, placing the intermediate ceramic green body in a mold, pressing it flat and heating the mold to 150°C, hot pressing it at a controlled pressure of 17 MPa and maintaining the pressure for 33 minutes, and then sintering it under nitrogen protection to obtain a finished ceramic green body.
[0051] Example 3
[0052] A green and environmentally friendly ceramic green mud, the ceramic green mud specifically comprises the following raw materials in parts by weight:
[0053]
[0054] The ceramic green mud also includes anhydrous ethanol.
[0055] The green and environmentally friendly method for manufacturing ceramic clay specifically comprises the following steps:
[0056] S1, grinding limestone, cordierite powder, shale powder, slag, wollastonite ore and iron powder by planetary ball mill for 60 min, passing through a 50-mesh sieve, and drying at 97.5° C. to obtain a dry mixed material; stirring anhydrous ethanol and phenolic resin uniformly to obtain a mixed material;
[0057] In the planetary ball mill, the material: ball: water = 1:1.6:1; the usage ratio of anhydrous ethanol and phenolic resin is 2mL:1.5g;
[0058] S2, the dry mixture, β-tricalcium phosphate and starch are mixed evenly, ground, passed through an 80-mesh sieve, anhydrous ethanol is added, stirred evenly and shaken, and then the mixture is added to a water bath with a temperature control of 82.5° C. and stirred until the anhydrous ethanol evaporates, and then the temperature is controlled at 87.5° C. and dried to obtain an intermediate ceramic green mud;
[0059] The amount of anhydrous ethanol added is 1.8 times the total mass of the dry mixture, β-tricalcium phosphate and starch;
[0060] S3, placing the intermediate ceramic green body in a mold, pressing it flat and heating the mold to 147.5°C, hot pressing it at a controlled pressure of 18 MPa and maintaining the pressure for 30 minutes, and then sintering it under nitrogen protection to obtain a finished ceramic green body.
[0061] Comparative Example 1
[0062] Compared with Example 3, the difference is that in Comparative Example 1, β-tricalcium phosphate is not added, and an equal weight portion of iron powder is used instead, and the remaining operating steps and parameters are the same.
[0063] Comparative Example 2
[0064] Compared with Example 3, the difference is that in Example 2, no iron powder is added, and an equal weight portion of β-tricalcium phosphate is used instead, and the remaining operating steps and parameters are the same.
[0065] Comparative Example 3
[0066] Compared with Example 3, the difference is that starch is not added in Comparative Example 3, and the other operating steps and parameters are the same.
[0067] Comparative Example 4
[0068] Compared with Example 3, the difference is that no phenolic resin is added in Comparative Example 4, and the other operating steps and parameters are the same.
[0069] Comparative Example 5
[0070] Compared with Example 3, the difference is that in Comparative Example 5, no limestone is added, and cordierite powder, shale powder, slag and wollastonite ore are used instead of limestone at 1 / 4 weight part, respectively, and the other operating steps and parameters are the same.
[0071] Comparative Example 6
[0072] Compared with Example 3, the difference is that in Comparative Example 6, cordierite powder is not added, and 1 / 4 weight part of the cordierite powder is used instead of limestone, shale powder, slag and wollastonite ore, respectively, and the other operating steps and parameters are the same.
[0073] Comparative Example 7
[0074] Compared with Example 3, the difference is that in Comparative Example 7, shale powder is not added, and 1 / 4 weight part of shale powder is used instead of limestone, cordierite powder, slag and wollastonite, and the other operating steps and parameters are the same.
[0075] Comparative Example 8
[0076] Compared with Example 3, the difference is that in Comparative Example 8, no slag is added, and 1 / 4 weight part of the slag is used instead of limestone, cordierite powder, shale powder and wollastonite ore, respectively, and the other operating steps and parameters are the same.
[0077] Comparative Example 9
[0078] Compared with Example 3, the difference is that in Comparative Example 9, wollastonite ore is not added, and 1 / 4 weight part of wollastonite ore is used instead of limestone, cordierite powder, shale powder and slag, respectively, and the other operating steps and parameters are the same.
[0079] Test Example 1
[0080] Degradability test: The weight loss rate was determined by weighing the ceramic green clay obtained in Examples 1-3 and Comparative Examples 1-4, soaking them in a 1 mol / L hydrochloric acid aqueous solution at room temperature for 144 hours, taking them out and drying them, weighing them again, and calculating the weight loss rate. The results are shown in Table 1.
[0081] Table 1
[0082] Weight loss rate (%) Example 1 12.5 Example 2 12.2 Example 3 12.6 Comparative Example 1 6.2 Comparative Example 2 7.0 Comparative Example 3 7.3 Comparative Example 4 8.4
[0083] It can be seen from Table 1 that the finished clay product prepared by the present invention has excellent degradability.
[0084] Test Example 2
[0085] Flexural strength test: The flexural strength test of the ceramic green clays prepared in Examples 1-3 and Comparative Examples 5-9 was performed according to GB / T 4741-1999. The results are shown in Table 2.
[0086] Table 2
[0087] Flexural strength(MPa) Example 1 1.47 Example 2 1.43 Example 3 1.53 Comparative Example 5 1.18 Comparative Example 6 1.23 Comparative Example 7 1.20 Comparative Example 8 1.02 Comparative Example 9 1.07
[0088] It can be seen from Table 2 that the green mud product prepared by the present invention has outstanding flexural strength. Specifically, this is because the present invention selects limestone, cordierite powder, shale powder, slag and wollastonite as the main raw materials and adjusts the ratio of each raw material in the formula, using limestone to strengthen the skeleton, cordierite powder to improve the density and strength of the ceramic, and shale powder to facilitate the nucleation and growth of crystals in the liquid phase; alkali metal oxides are introduced into slag and wollastonite to promote the process of liquid phase sintering; therefore, the five can synergistically make the green mud have outstanding flexural strength.
[0089] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0090] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A green and environmentally friendly ceramic clay, characterized in that: The ceramic green mud specifically comprises the following raw materials in parts by weight:
2. The green and environmentally friendly ceramic clay according to claim 1, characterized in that: The average particle size of the beta-tricalcium phosphate is 360 nm; the starch is soluble starch with an average particle size of 60 meshes; and the phenolic resin is a thermosetting phenolic resin.
3. The green and environmentally friendly ceramic clay according to claim 1, characterized in that: The ceramic green mud also includes anhydrous ethanol.
4. A method for producing green and environmentally friendly ceramic clay according to claim 3, characterized in that: The specific steps include: S1, grinding limestone, cordierite powder, shale powder, slag, wollastonite ore and iron powder with a planetary ball mill, sieving, and drying under temperature control to obtain a dry mixed material; stirring anhydrous ethanol and phenolic resin to obtain a mixed material; S2, the dry mixture, β-tricalcium phosphate and starch are mixed evenly, ground, sieved, anhydrous ethanol is added, stirred evenly and shaken, and then the mixture is added to a temperature-controlled water bath and stirred until the anhydrous ethanol evaporates, and the temperature is controlled and dried to obtain an intermediate ceramic green mud; S3, placing the intermediate ceramic green body in a mold, flattening the mold, heating the mold, controlling the pressure to form the green body through hot pressing and maintaining the pressure, and then sintering the green body under nitrogen protection to obtain a finished ceramic green body.
5. The method for producing green and environmentally friendly ceramic clay according to claim 4, characterized in that: In the planetary ball mill of step S1, the ratio of material: ball: water is 1:1.2-2:1, and the ball milling time is 30-60 min; the usage ratio of anhydrous ethanol and phenolic resin is 2 mL:1-1.5 g.
6. The method for producing green and environmentally friendly ceramic clay according to claim 4, characterized in that: The sieving in step S1 is through a 50-mesh sieve; the temperature of the temperature-controlled drying is 95-100°C.
7. The method for producing green and environmentally friendly ceramic clay according to claim 4, characterized in that: The amount of anhydrous ethanol added in step S2 is 1.4-1.8 times the total mass of the dry mixture, β-tricalcium phosphate and starch.
8. The method for producing green and environmentally friendly ceramic clay according to claim 4, characterized in that: The sieving in step S2 is through an 80-mesh sieve; the temperature of the temperature-controlled water bath stirring is 80-85°C; the temperature of the temperature-controlled drying is 85-90°C.
9. The method for producing green and environmentally friendly ceramic clay according to claim 4, characterized in that: In step S3, the mold is heated to 145-150°C.
10. The method for producing green and environmentally friendly ceramic clay according to claim 4, characterized in that: The pressure of the controlled pressure hot pressing molding and pressure holding in step S3 is 16-18 MPa, and the time is 30-35 minutes.
Citation Information
Patent Citations
Degradable environmentally-friendly ceramic product and method for producing same
CN101891450A
Method for preparing environment-friendly honeycomb ceramic heat accumulator by use of waste slag
CN103992099A
Degradable bioactive ceramic / metal composite material, method for preparing same and application of degradable bioactive ceramic / metal composite material
CN105879122A
Degradable green environment-friendly ceramic flowerpot and manufacturing method
CN115636658A
Environmentally safe and biodegradable composition for manufacturing the skeet target which is used for trapshooting, as well as it's application
WO2001053231A1